2022
DOI: 10.1177/07334648221130677
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Home Health Aides’ Perspectives towards COVID-19 Vaccination

Abstract: Home health aides provide care to homebound older adults and those with chronic conditions. Aides were less likely to receive COVID-19 vaccines when they became available. We examined aides’ perspectives towards COVID-19 vaccination. Qualitative interviews were conducted with 56 home health aides at a large not-for-profit home care agency in New York City. Results suggested that aides’ vaccination decisions were shaped by (1) information sources, beliefs, their health, and experiences providing care during COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…9,34 Recognizing this cultural context could potentially play a role in how financial incentives are viewed, which is supported by prior research. 9 In addition to financial incentives, prior research on vaccine hesitancy in HHAs also found workers expressed skepticism toward vaccine mandates. 9 Given that the HHW workforce is largely women of color, monetary incentives and mandates may paradoxically raise red flags and decrease trust in this population.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…9,34 Recognizing this cultural context could potentially play a role in how financial incentives are viewed, which is supported by prior research. 9 In addition to financial incentives, prior research on vaccine hesitancy in HHAs also found workers expressed skepticism toward vaccine mandates. 9 Given that the HHW workforce is largely women of color, monetary incentives and mandates may paradoxically raise red flags and decrease trust in this population.…”
Section: Discussionmentioning
confidence: 82%
“…While some HHWs voiced appreciation of the $100 incentive offered by NYC, hesitant workers in our study group overall felt skepticism toward a government-funded incentive. It is important to note the historical context of unethical experimentation and exploitation in the United States of people who identify as Black, indigenous, and people of color, such as with the Tuskegee Study, as well as personal encounters with the health care system, which may contribute to mistrust in the medical system 9,34 . Recognizing this cultural context could potentially play a role in how financial incentives are viewed, which is supported by prior research 9 .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations